The Parliamentary Immunity of Members of the National Assembly under the Constitution of the Kingdom of Thailand B.E. 2560 (2017) - Sitthiphram, Natthaphon (Rajapark Journal, 2021)
National Assembly in comparison with rights of a victim or a defending State in a criminal case. The paragraph 3 of the aforesaid section indicates that, before the beginning of a parliamentary session, if a member of the Assembly is detained prior to this session, the President of the Assembly has discretion to request a responsible authority to release such member without any commitment from the House of Representative or the Senate which such member belongs. In addition, although this section allows the House of Representative or the Senate, where the accused member has membership, to vote for the provision of the immunity, it does not specify a preliminary examination to filter the facts before voting. In other words, the parliamentary immunity provision without filtration mechanism has become Thailand’s parliamentary tradition. This provision is inappropriate and inconsistent towards the purposes of the Constitution. Therefore, Section 125 should be amended by adding the immunity withdrawal principle in the case that a fact or circumstance has changed after providing the immunity. The withdrawal principle should be adapted from the concepts, means, and methods of foreign Constitutions.